Tillering propensity and crop water use of different sorghum varieties under varying irrigation regimes - Mathatha, Rifilwe (My University, 2025)
Tillering is one of sorghum’s adaptive traits to water availability, which can ‘make or break’ crop yields depending on cultivar genetics. The complex interaction between water availability and genetic expression makes tiller contribution to yield difficult to be predicted and quantified. Additionally, contributions of sorghum tillers and main stem to ‘yield per drop’ and water use under different water availability and sorghum cultivars have not been quantified. Therefore, this study aimed to evaluate tillering propensity and water use of sorghum cultivars under complex tiller regulating practices, hence showcasing tiller contribution to sorghum yields and their water productivity under different sorghum cultivars and varying irrigation regimes. A literature review on practices and factors that regulate tillering was done to provide guidelines on the key practices and factors that regulate tillering in sorghum to enhance the productivity of tillers and yield. Highlighting the effective management practices that can improve grain yield by prioritising resource allocation hence minimizing competition among tillers. Moreover, the study emphasized that the dynamics of tillering must be understood under varying management practises to maximize the tiller contribution to yield and ‘yield per drop’. As such, the field trial was conducted to quantify the tiller contributions to yield, water use, and water productivity at the University of Limpopo experimental farm. The study was carried out as a 3 x 4 factorial, laid out as a split-plot and arranged in a randomized complete block design (RCBD). The plots comprised of two irrigation regimes assigned as the main (full, deficit) which were compared to rainfed (unirrigated control), and four sorghum cultivars as subplots (Mr Buster, PAN606, Macia, and a local landrace) replicated three times. For addressing the tiller contributions to yield, water use and water productivity, phenological development, maximum canopy cover, plant height, stem width, biomass accumulation, number of tillers and fertile tiller percentage, harvest index, grain yield, soil water content, evapotranspiration, water productivity and the tiller contributions were collected during the growing season. The interactive effects of cultivar selection and irrigation regimes significantly influenced shoot dry biomass, grain yield, water use, and water productivity. Significantly higher shoot dry biomass (5.70 ton/ha), grain yield (7.10 ton/ha), and water productivity (2.58 kg/m3 ) were recorded from the local landrace when it was cultivated under deficit irrigation. On the contrary, the lowest sorghum yield (3.04 ton/ha), shoot dry biomass (1.78 ton/ha), and xiii water productivity (1.19 kg/m3 ) was obtained by Mr Buster with high water use (239.9 mm). However, it had statistically comparable water use and water productivity with PAN606 (225.5 mm and 1.34 kg/m3 ) and Macia (226.2 mm and 1.24 kg/m3 ), respectively. The great performance of landrace was attributed to longer maturity, number of tillers produced and the adaptability to local environment. The landrace had high percentage of fertile tillers (81%) compared to Mr Buster (51%). This suggest that landrace is good at using low water to produce reasonable yield and can be planted to maximize yield with less water used. Tillers made a substantial contribution to both overall grain yield and water productivity, accounting for 57% of the total yield compared 43% contribution of the main stem. Similarly, tillers contributed 53% to water productivity, while the main stem contributed 47%. Despite this, the main stem remained the statistically dominant yield contributor across different irrigation regimes and cultivars. The early-emerging tillers T1 (27 %), T2 (15 %), and T3 (9 %) proved to be the most productive due to better access to plant available assimilates. In contrast, the later-emerging tillers T4 (4 %) and T5 (2 %) were less competitive and had a minimal impact on yield, as they had low access to the resources needed by the plant. The reported tiller contributions to yield ranges from 5 – 78 %, hence, the conclusion was drawn that tillers contributing less than 5% to yield are considered non-significant. Additionally, tiller 1 to tiller 3 consistently contributed within a range of 5 – 78% across all irrigation regimes and cultivars. Therefore, it is suggested that farmers prioritize harvesting tillers up to tiller 3, as tillers beyond this point (tiller 4 and tiller 5) do not contribute significantly to overall yield. It is then recommended that cultivating landrace under deficit irrigation and focusing on tillers up to tiller 3, could achieve sustainable yields and maximize the contributions of productive tillers. However, the study was limited to a single site and season planting. Therefore, it is recommended that future research include multi-location trials and multiple growing seasons to capture the spatial and temporal variability of environmental conditions. Furthermore, additional research should explore specific agronomic practices designed to selectively boost the productivity of tillers while reducing the presence of unproductive ones
Thesis (M. Agricultural Management (Plant Production)) -- University of Limpopo, 2025
Keywords: Food security; Irrigation regimes; Sorghum cultivar; Tiller contributions; Water productivity; Yield; Evapotranpiration; Evapotranspiration; Plants -- Water requirement; Food security -- Climatic factors; Water-supply; Sorghum; Sorghum -- Irrigation